2022
DOI: 10.1039/d2dt02460h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning ESIPT-coupled luminescence by expanding π-conjugation of a proton acceptor moiety in ESIPT-capable zinc(ii) complexes with 1-hydroxy-1H-imidazole-based ligands

Abstract: The emission of the ESIPT-fluorophores is known to be sensitive to various external and internal stimuli and can be fine-tuned through the substitution in the proton-donating and proton-accepting groups. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 190 publications
1
12
0
Order By: Relevance
“…0.7 kJ mol −1 , the fluorescence of the tautomeric form is not observed in the emission spectra of HL due to the presence of an efficient non-radiative deactivation pathway through a S T 0 /S T 1 conical intersection. This study and our recent studies 108,135 have shown that ESIPT-dyes based on 1-hydroxy-1 H -imidazole tend to demonstrate abnormal luminescence phenomena, essentially contributing to the photophysics of proton transfer systems in general.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…0.7 kJ mol −1 , the fluorescence of the tautomeric form is not observed in the emission spectra of HL due to the presence of an efficient non-radiative deactivation pathway through a S T 0 /S T 1 conical intersection. This study and our recent studies 108,135 have shown that ESIPT-dyes based on 1-hydroxy-1 H -imidazole tend to demonstrate abnormal luminescence phenomena, essentially contributing to the photophysics of proton transfer systems in general.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, HL-A can undergo the ESIPT process (Scheme 6) and can exist in two forms: in the normal form (N) with the proton at the O1 atom of the 1-hydroxy-1Himidazole moiety and in the tautomeric (T) form with the proton at the O2 atom of the benzoyl moiety. Although planar molecular geometries ensure the best p-conjugation and seem to stabilize the molecule to the greatest extent (like in the previously reported 1-hydroxy-1H-imidazole-based ESIPT emitters with nitrogen-containing proton-accepting groups 108,135 ), none of the optimized conformers are planar. Short van der Waals C-HÁ Á ÁO and C-HÁ Á ÁH-C contacts and repulsive forces of the lone pairs of two oxygen atoms tend to increase the C19-C14-C5-N1 and N3-C2-C6-C7 torsions and reduce the p-conjugation for all conformers.…”
Section: Theoretical Analysis Of the Absorption And Emission Mechanis...mentioning
confidence: 76%
“…Electronic properties of ESIPT-capable molecules and therefore the ESIPT and GSIPT abilities of such molecules can be tuned through introducing various substituents or heteroatoms, expanding the p-system, [37][38][39][40] binding metal ions, [41][42][43][44][45][46][47][48][49][50][51][52][53][54] protonation/deprotonation, [55][56][57][58][59][60][61][62][63][64] solvent effects, [65][66][67][68][69] etc. The synthetic flexibility of such molecules is based on established synthetic methods of organic chemistry and provides researchers with almost unlimited options for the rational design and modification of various ESIPT-capable scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, we found out that the replacement of a proton-accepting 2-(pyridin-2-yl) group in the structure of the HL p ligand with a more π-conjugated proton-accepting 2-(quinolin-2-yl) group results in a noticeable red-shift of the fluorescence bands of HL q ( λ max = 640 nm) and [Zn(HL q )X 2 ] ( λ max = 591 nm) compared with the fluorescence bands of HL p ( λ max = 575 nm) and [Zn(HL p )X 2 ] ( λ max = 537 nm). 132 The reason underlying the red-shift of the emission band is the stabilization of the T-form in the case of the HL q / [Zn(HL q )X 2 ] compounds with extended π-conjugation of the proton-accepting moiety. To understand the driving force for such stabilization, we carried out Merz–Singh–Kollman atomic charge analysis and discovered that the negative charge on the proton-accepting nitrogen atom increases on going from HL p / [Zn(HL p )X 2 ] to HL q / [Zn(HL q )X 2 ] , while the positive charge on the proton increases (Fig.…”
Section: Resultsmentioning
confidence: 99%